Conjunctive functionalization of vinyl boronate complexes with electrophiles: a diastereoselective three-component coupling. Issue 36 (20th April 2017) - Armstrong, Roly J.; Sandford, Christopher; García-Ruiz, Cristina; Aggarwal, Varinder K.
Abstract : A conjunctive functionalization process enables a diastereoselective three-component coupling of vinyl boronate complexes with a range of electrophiles. Abstract : A method for the conjunctive functionalization of vinyl boronate complexes with electrophiles is described. The overall process represents a three-component coupling between a vinyl boronic ester, carbon nucleophile and an electrophile, thus affording complex multifunctionalized products from simple starting materials. The diastereoselectivity ( syn or anti ) of this process is strongly dependent upon the nature of the electrophile.